Some Yoruba quantifier words and semantic interpretation a reply to a critique - Adenike S. Lawal (Studies in African Linguistics, 1989)
The empirical support for Adewole's critique of my paper (in this issue), "Some Yoruba quantifier words and semantic interpretation" [LawaI 1986], comes from a literary text Atoto Arere [Adewole p. 4]. Adewole's approach, which is characteristic of traditional or taxonomic linguistics, has been found to be most unreliable in dealing with questions of empirical fact and is strongly rejected in present day linguistics. Our study of the semantic interpretation of some Yoruba quantifier words was based on native speaker judgements/tests, specifically Y oruba speakers in Horin township of Kwara State of Nigeria.